2011
DOI: 10.1038/ncomms1558
|View full text |Cite
|
Sign up to set email alerts
|

Global kinomic and phospho-proteomic analyses of the human malaria parasite Plasmodium falciparum

Abstract: The role of protein phosphorylation in the life cycle of malaria parasites is slowly emerging. Here we combine global phospho-proteomic analysis with kinome-wide reverse genetics to assess the importance of protein phosphorylation in Plasmodium falciparum asexual proliferation. We identify 1177 phosphorylation sites on 650 parasite proteins that are involved in a wide range of general cellular activities such as DnA synthesis, transcription and metabolism as well as key parasite processes such as invasion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
531
3
12

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 334 publications
(561 citation statements)
references
References 44 publications
15
531
3
12
Order By: Relevance
“…These cells accumulate in the insect's salivary gland, where they are primed for infection of a novel human host. Stage transitions during this complex life cycle are likely to require efficient signalling pathways, and evidence for the role of protein phosphorylation in life-cycle progression is emerging [18][19][20].…”
Section: Introduction (A) Malaria: Disease Status Need For New Contrmentioning
confidence: 99%
“…These cells accumulate in the insect's salivary gland, where they are primed for infection of a novel human host. Stage transitions during this complex life cycle are likely to require efficient signalling pathways, and evidence for the role of protein phosphorylation in life-cycle progression is emerging [18][19][20].…”
Section: Introduction (A) Malaria: Disease Status Need For New Contrmentioning
confidence: 99%
“…The phospho-null mutant S610A of the PfAMA1 tail was also able to complement (Santos et al, 2011). In the phospho-proteomes published by Treeck et al (2011) andSolyakov et al (2011), S610 was confirmed as well as 4 additional sites in the tail, and two new phosphorylated serine residues were identified in TgAMA1 ( Fig. 1 and Table S1).…”
Section: Moving Junction Formationmentioning
confidence: 73%
“…Furthermore, Go 6983, a PKC inhibitor (PfPKB catalytic domain is closely related to PKC) is able to affect in vitro recombinant PfPKB activity and reduce the ability of P. falciparum to invade erythrocytes (Kumar et al, 2004). Consistent with a vital role in parasite development, both PKB and CDPK1 are refractory to gene disruption in P. berghei and P. falciparum (Kato et al, 2008;Solyakov et al, 2011;Tewari et al, 2010). Using a broad-range serine/threonine kinase inhibitor (staurosporine), a marked reduction of phosphorylation of PfGAP45 was observed (Jones et al, 2009).…”
Section: Glideosome: Myosin Motor Assembly and Functionmentioning
confidence: 86%
See 2 more Smart Citations